Comparison of a modified large-particle method with some high resolution schemes. One-dimensional test problems - Sadin, D.V.; Davidchuk, V.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2019)
The paper presents a comparative analysis of the computational properties of a modified large-particle method on one-dimensional gas dynamics test problems in a wide range of flow parameters. The numerical results are compared with self-similar solutions and data obtained by high-resolution schemes from the second to the sixth order of approximation. It is shown that the presented scheme is numerically efficient and competitive.